The Prices and Incomes Commission in Retrospect - Anton, F. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
In this article, the author reviews the Canadian Prices and Incomes Commission's findings and comments on some of the conclusions drawn